THE EVOLUTION OF PROSTHETIC LIMBS AND THEIR ROLE IN AMPUTEE ATHLETES' PERFORMANCE - Mosaed, Mohammed S.; Zarikar, Kalpana B. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The evolution of prosthetic limbs has significantly reshaped the landscape of athletic performance for amputee athletes. This paper examines how advancements in prosthetic technology, such as carbon fiber running blades, bionic limbs, and myoelectric prosthetics, have enhanced performance, allowing athletes to engage in competitive sports at elite levels. Through a qualitative review of existing literature, this study synthesizes key technological developments, the biomechanical benefits of modern prosthetics, and the psychological impact on amputee athletes. The review also includes an exploration of wearable technologies, which support performance tracking and training optimization. Additionally, the paper delves into the challenges related to cost and accessibility while looking at the future potential of prosthetic innovations in sports. By analyzing case studies and expert perspectives, this research provides insights into the transformative role of prosthetics in breaking barriers for amputee athletes.